Vozes e escritas femininas em Angola: a luta pela sobrevivência e emancipação de mulheres (1961-2002) - Dias, Helenice Moreira (2013)
This research aims to suggest an interpretation of the female narratives about the daily struggles in Angola between the war of independence (1961-1974) and the civil war (1975- 2002). Therefore, we emphasize some female marks, i.e., the life experience of women over the armed conflicts as well as during the peace process and national reconstruction. By means of the female narratives contained in the book O Livro da Paz da Mulher Angolana, organized by Dya Kasembe and Paulina Chiziane, we intend to comprehend the dimensions of tradition, oppression and emancipation as a way to understand the challenges faced by women before, during and after the conflicts. We define these questions based on the observation of the narratives as well as the books written by the Angolan writer Dya Kasembe. In this way, we aim to reverberate these narratives in order to learn more about the Angolan female s universe which has been relegating by the established historiography. To sum up, we try to listen to what these women are talking, feeling and thinking